Dissociation of periodic leg movements from arousals in restless legs syndrome - Manconi, Mauro; Ferri, Raffaele; Zucconi, Marco; Bassetti, Claudio L.; Fulda, Stephany; Aricò, Debora; Ferini-Strambi, Luigi (Annals of neurology, 2012)
Objective: The purpose of this study was to characterize the nature of the relation between periodic leg movements during sleep (PLMS) and cortical arousals to contribute to the debate on the clinical significance and treatment of PLMS. Methods: A prospective, placebo‐controlled, single‐blind, parallel group study was carried out including 46 drug‐naive patients with idiopathic restless legs syndrome (RLS). Each patient underwent 2 consecutive full‐night polysomnographic studies. The first night was the baseline night. Prior to the second night, 1 group received a single oral dose of 0.25mg pramipexole, whereas a second group received a single oral dose of 0.5mg clonazepam, and the remaining patients received placebo. Sleep stages, cyclic alternating pattern (CAP), and leg movement activity were scored following standard criteria; symptoms of RLS were also assessed. Results: Pramipexole suppressed PLMS without affecting electroencephalographic (EEG) instability (CAP) and arousals (corresponding to CAP A3 and, partially, A2 subtypes), whereas clonazepam did the opposite, reducing non‐rapid eye movement sleep EEG instability without effects on PLMS. Both drugs were effective on sensory RLS symptoms. Interpretation: This study demonstrates that a selective pharmacological approach can disconnect PLMS from arousal events, suggesting an indirect relation between each other. These results might weaken the hypothesis of a direct pathological role of PLMS in sleep disruption and can be important for the discussion on the existence of a distinct entity called periodic limb movements disorder. Moreover, the study opens the doors to the possibility of a joint treatment for RLS targeting sensory and motor symptoms, as well as sleep instability. ANN NEUROL 2012;71:834–844